Application of recommendation system with AHP method and sentiment analysis - Ira Prasetyaningrum; Kholid Fathoni; Tri Tangguh Jiwo Priyantoro (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
Over time, people needs are increasing. Needs that must be met, often cause problems in the people in determining a choice. People must make the right choice and according to their needs. Not an easy thing for people to make these choices. Therefore, a recommendation system is needed to support people in making decisions that fit their criteria. This research provides a system that can provide recommendations for decision support people according to their criteria, which are web-based. The decision-making system in this research uses the analytical hierarchy process (AHP) method. AHP is a multi-criteria decision-making method, which in this research one of the criteria is using sentiment analysis. Sentiment analysis is the process of understanding, extracting, and processing textual data to get sentiment information from an opinion sentence. The opinion sentiment value of each alternative will be included in the AHP calculation to get the best alternative recommendations according to the criteria of people. The result of this research is that the system can provide recommendations to people or users according to their criteria and alternatives as well as public opinion about each alternative.